Employee Experiences with Digital HRM Technologies: A Critical Scoping Review - Hennayake, Hennayake Mudiyanselage Nadeeka Shayamali (Auckland University of Technology, 2025)
In the last decade, the Human Resource (HR) function has transformed its operations through the introduction of digital technologies. The drivers for this change are – increased efficiency and improved experience throughout the employee life cycle. This includes identifying suitable candidates, onboarding, training, retention, performance and promotion of an employee. Digital HRM further evolved with an emergence Artificial Intelligence (AI) and IoT (Internet of Things), with the promise to deliver better outcomes such as cost savings and process automation to the organization. However, the success of digital HRM technology largely depends on employee perception, adoption, and optimal use. From the existing literature, this study aims to find if employee perceptions and experiences were studied in-depth or the literature was just focused on finding the organizational positive outcomes by answering four research questions (RQs), that include employee perceptions and experiences with digital HRM technologies as a RQ1, the elements that influence employee acceptance or resistance of digital HRM as a RQ2, the impact of digital HRM on employee productivity, engagement and job satisfaction as a RQ3, finally, the positive and negative impacts of digital HRM with organizations and employees as a RQ4. A scoping review using systematic search and selection methods identified 25 peer reviewed articles between 2014 till 2024 that asked about how employees experienced HRM Technology. The studies indicated digital HRM technologies have brought organizational efficiency, cost savings, increased employee engagement, and productivity. However, there were only a handful of studies that provided an in-depth focus on employee perceptions and experiences. The critical contribution from this scoping review highlights the need for in-depth research examining the feelings of employees, especially the adverse effects that include data privacy, psychological impacts, gender bias, job insecurity, trust issues with technology, surveillance, social isolation, discomfort, and performance pressure. This study calls for a balanced investigation of digital HRM’s positive and negative impacts on employers and employees.
Keywords: Human Resource Management (HRM); Digital HRM; Artificial Intelligence (AI); Internet of Things (IoT); Perceptions; Experiences; Productivity; Engagement; Privacy; Psychological Impacts; Surveillance; Dehumanization